(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This article is based on the study of different types of food and their nutritive value and its importance in human to live healthy life. These nutrients nourish our body and keep us fit and healthy. They can minimize risk of many chronic diseases. Nutrients, which are source of energy essential for our bodies building, are classified as carbohydrates, fats, fiber, minerals, proteins, vitamins and water. Foods that are naturally rich in nutrient include fruits and vegetables, lean meats, fish, whole grains, dairy products, legumes, nuts, and seeds also are high in nutrients. Foods containing rich nutrient are low in sugar, sodium, starches, and bad fats. They contain lot of vitamins and minerals and very few calories. Our body needs vitamins and minerals, known as micronutrients. Daily food intake and nutritional value can influence our overall health over long period of time.